Effect of Rebon Shrimp-Based Supplementary Feeding on Height of Stunted Children - Sri Sulistyawati Anton; Agussalim Bukhari; Aidah Juliaty A. Baso; Kadek Ayu Erika (AIBPM Publisher, 2022)
In Indonesia, as other developing countries, stunting is still prevalent especially in children. Stunting significantly affects person's development in future. Stunting occurs about 162 million children under 5 years worldwide. It is generally caused by insufficient nutritional intake mostly on children from underprivileged families. Rebon-shrimp is a nutritious and inexpensive local food, but its utilization is still low. It is potential to be an additional food for children. This study aims to determine the effectiveness of rebon-shrimp based supplementary feeding on weight and height in malnourished children aged 24-60 months. This study is a quasi-experimental design, involving 88 malnourished children, divided into 2 groups, intervention (n=44) and control (n=44). The intervention group received rebon-shrimp based supplementary food for 90 days, while the control group received a placebo. Height was assessed at baseline and monthly follow-ups until endline at Day 90. The results were analyzed by repeated-measures anova test. There was a statistical difference (p<0.0001) in height gain on both groups, but the increase in height of children who received rebon products (3.94cm) was greater than children who did not receive rebon products (2.92cm). It was concluded that supplementary food made from rebon-shrimp was beneficial for increasing height of stunted children.Â Keywords: rebon-shrimp; supplementary food; stunted